Biology and Management of Fimbristylis Miliacea (L.) Vahl - Begum, Mahfuza (2006)
Most experiments were carried out in a glasshouse at Universiti Putra Malaysia, while the field survey was conducted in ricefields in the Muda area, Kedah. This study was initiated during March 2003 and ended on November 2005. The objectives of the study were to investigate the prevalence of F. miliacea in ricefields both above ground as well as in the soil seedbank, its emergence behaviour, life cycle, life table, competitive ability with rice, and its management.